Educação em tempo de crise - Adalberto Dias de Carvalho (Escola Superior de Educação de Paula Frassinetti, 2012)
The contemporary crisis, while generating poverty and unemployment, touches our existence: spreads insecurity, steals dignity, imposes suffering, and leads many people to live by surviving. But the crisis also brings a problem of meaning by threatening the horizon that guides us, the foundations that sustain us and hope that transcends us. It threatens also by demanding other horizons, other foundations, other forms to decline hope. It intensifies when these alternatives are slow to appear.